Seismic Discontinuities Across the North American Caribbean Plate Boundary From S‐to‐P Receiver Functions - Daniel Possee; Catherine Rychert; Nicholas Harmon; Derek Keir (Geochemistry, Geophysics, Geosystems, 2021)
Abstract The evolution of the Caribbean plate has resulted in the formation of volcanic arcs, the Caribbean Large Igneous Province (CLIP) and micro‐plates across the plate boundary zones. The northern plate boundary with the North American plate has been particularly segmented with the transition from oblique subduction to oblique collision moving from east to west. However, there are few constraints on the seismic structure of the upper mantle across the plate boundary. Here we use S‐to‐P receiver functions to map seismic velocity discontinuities across the plate boundary, placing constraints on crustal and lithospheric thicknesses, as well as the structures associated with subduction and collision. We image a velocity increase with depth, consistently seen at 28–34 ± 4 km along the plate boundary, which corresponds to the Moho. A second strong velocity increase with depth is observed at depths of 64–66 ± 5 km, which is related to the presence of subducting slabs and anisotropic effects. We image a velocity decrease with depth at 95–135 ± 7 km, which reflects a lithosphere‐asthenosphere boundary that varies in depth across the plate boundary. The deepest negative discontinuity spatially maps to the CLIP. We suggest that a deep melting depth at 135 km, associated with an elevated potential mantle temperature of 1585 ± 20°C during CLIP formation, caused a depleted and dehydrated root to the base of melting, thus thickening the lithosphere.